2004
DOI: 10.1161/01.cir.0000115586.25803.d5
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Targeted Myocardial Contrast Echocardiography Can Assess the Degree of Acute Allograft Rejection in a Rat Cardiac Transplantation Model

Abstract: Background-Repetitive endomyocardial biopsies are necessary to monitor the effects of immunosuppressants after cardiac transplantation. Contrast ultrasound with microbubble targeting of leukocytes detects acute leukocyte infiltration. We examined whether leukocyte-targeted myocardial contrast echocardiography (MCE) could provide for the quantitative assessment of acute cardiac rejection. Methods and Results-Hearts from Brown Norway rats or Lewis rats were transplanted into other Brown Norway rats. Isografts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…30 Our results are in line with earlier reports that show that CEU molecular imaging can detect cardiac transplant rejection by targeting activated leukocytes or intercellular adhesion molecule-1. 31,32 However, whereas the inflammatory process in transplant rejection shares similarities with myocarditis, an important difference that increases the diagnostic challenges is the low grade and focal nature of the inflammatory infiltrate in moderate myocarditis ( Figure 2B and 2E). Also, the finding that CEU molecular signal for both leukocyte-targeted and P-selectin-targeted MB was greater in severe compared with moderate myocarditis indicates that various degrees of disease activity can be discerned.…”
Section: Ceu Molecular Imaging Detects Myocarditis Independent Of Funmentioning
confidence: 99%
“…30 Our results are in line with earlier reports that show that CEU molecular imaging can detect cardiac transplant rejection by targeting activated leukocytes or intercellular adhesion molecule-1. 31,32 However, whereas the inflammatory process in transplant rejection shares similarities with myocarditis, an important difference that increases the diagnostic challenges is the low grade and focal nature of the inflammatory infiltrate in moderate myocarditis ( Figure 2B and 2E). Also, the finding that CEU molecular signal for both leukocyte-targeted and P-selectin-targeted MB was greater in severe compared with moderate myocarditis indicates that various degrees of disease activity can be discerned.…”
Section: Ceu Molecular Imaging Detects Myocarditis Independent Of Funmentioning
confidence: 99%
“…Two studies have been reported to investigate transplant rejection in vivo in animal models. The first study employed passively leukocyte-targeted microbubbles with phosphatidylserine to assess acute allograft rejection in a rat cardiac transplantation model [68]. The degree of rejection in transplanted hearts could be directly revealed by the magnitude of intramyocardial infiltration of macrophages and T lymphocytes due to accumulation of targeted microbubbles at the site of inflammation.…”
Section: Molecular Ultrasound Imaging Of Inflammationmentioning
confidence: 99%
“…24 The initial in vivo study demonstrating the ability of CEU to 25 This study demonstrated a 10-fold increase in ICAM-1-targeted microbubble signal compared to control signal and corresponded to grade III to IV rejection on immunohistochemistry in concert with an elevated expression of ICAM-1 (Figure 4). In a similar murine model of acute cardiac rejection, molecular imaging of activated leukocytes was performed using nontargeted microbubbles, 26 thus relying on the nonspecific interactions of activated leukocytes to microbubbles via integrin-and complement-mediated pathways. 3 The degree of CEU signal from activated leukocytes was proportional to the degree of histologic inflammation, rejection grade, and inversely proportional to the degree of immune suppression treatment.…”
Section: Targeting Acute Transplant Rejectionmentioning
confidence: 99%